Effects of fully immersive virtual reality training on cognitive function in patients with mild cognitive impairment: a systematic review and meta-analysis - Yu, Jing; Song, Jingru; Shen, Qin (Frontiers in Human Neuroscience, 2024)
BackgroundMild cognitive impairment (MCI) is a prodromal stage of dementia. There is no specific medication to slow the progression of MCI. Recent studies have confirmed the positive effects of virtual reality (VR). However, the results are inconsistent due to different types of VR interventions, small sample sizes, and the varying quality of the literature. This study aimed to assess the effects of fully immersive VR on cognitive function in MCI patients.MethodsA systematic review of published literature was conducted using PubMed, Cochrane Library, Embase, CINAHL, Web of Science, SinoMed, CNKI, Wanfang, and VIP Database. The search period was from inception through March 1, 2024. Eligible studies were randomized controlled trials evaluating the effects of fully immersive virtual reality training on cognitive function in MCI patients. Two investigators independently performed literature screening, data extraction, and quality assessment; a meta-analysis of the included literature was performed using RevMan 5.4. The Cochrane Risk of Bias tool was used to assess the methodological quality.ResultsA total of 11 randomized controlled trials with 525 patients were included. The meta-analysis showed that fully immersive virtual reality training had significant effects on global cognitive function (MD = 2.34, 95% CI [0.55, 4.12], p = 0.01); (MD = 0.93, 95% CI [0.30, 1.56], p < 0.01), executive function (SMD = -0.60, 95% CI [−0.84, −0.35], p < 0.01), and attention (MD = 0.69, 95% CI [0.15, 1.23], p = 0.01). Still, the difference in memory (SMD = 0.27, 95% CI [−0.24, 0.78], p = 0.30) was not statistically significant. Subgroup analyses showed that executive function could be improved only when the intervention duration was ≥40 h. In contrast, excessive training (≥30 times) was counterproductive.ConclusionFully immersive virtual reality training improved cognitive functioning, executive functioning, and attention in MCI patients but was less effective in improving memory. Subgroup analysis suggests that fully immersive VR training must ensure sufficient intervention duration while avoiding frequent interventions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO (CRD42024498629).